The role of clusters in the development of Hungarian city-regions - Imre Lengyel (European Regional Science Association (ERSA), 2010)
More and more scholars of regional science are interested nowadays in the question what role do clusters in city-regions play in the knowledge-based economy. This question can be dealt with from the functional or nodal regions point of view and one has to examine the factors that influence regional competitiveness. The answers are especially important for the Hungarian city-regions, since between 2007 and 2013 they are aimed with significant subsidies from EU regional development funds to improve their competitiveness. In this paper we outline our analytical framework: the pyramid model of regional competitiveness. After this the paper assesses the competitiveness types of the Hungarian functional subregions, as city-regions (LAU1). A complex methodology, with the help of multi-variable data analysing methods, is used throughout our statistical analysis to underlie the classification of city-regions. For the clusters mapping in these regions we apply the location quotient (LQ) method.
Keywords: 330; regional competitiveness; cluster-based regional economic development; cluster mapping; LQmethod